PENAMBAHAN TEPUNG DAUN SINGKONG DALAM PEMBUATAN KERUPUK SAGU - Berlio ' Mandriali; Usman ' Pato; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aim was to get the best formulation in making sago crackers by adding cassava leaves flour. Research was conducted by using a Completely Randomized Design (CRD) experiment with five treatments and three repetitions. The treatments in this research were K0 (Sago starch 100% : cassava leaves flour 0%), K1 (Sago starch 95% : cassava leaves flour 5%), K2 (Sago starch 90% : cassava leaves flour 10%), K3 (Sago starch 85% : cassava leaves flour 15%) and K4 (Sago starch 80% : cassava leaves flour 20%). Data were analyzed statistically by using ANOVA and tested further by using DNMRT at 5% level. Research result showed that the ratio of sago starch and cassava leaves flour significantly affected the water moisture, ash, fiber and carbohydrate contents as well as the swelling power and the sensory descriptive and overall hedonic test. The best treatment in this research was crackers in treatment K1 (sago starch 95% : flour cassava leaves 5%), which had moisture content of 12.37%, ash content 0.26%, 1.01% fiber content, carbohydrate content 54.72% and swelling power 64.57%. Furthermore, sensory assessment showed a little green color, rather distinctive smells of cassava leaves, tasteless cassava leaves and a bit crispy as well as overall preference by panelists expressed a little liked the selected crackers. Keywords: sago starch, cassava leaves flour , crackers